Tau or neurofilament light—Which is the more suitable biomarker for Huntington’s disease? - Niemelä, Valter; Landtblom, Anne-Marie; Blennow, Kaj; Sundblom, Jimmy (PloS one, 2017)
Previous studies have suggested cerebrospinal fluid (CSF) levels of neurofilament light (NFL) and total tau are elevated in Huntington's disease (HD) and may be used as markers of disease stage. Biomarkers are needed due to the slow disease progression and the limitations of clinical assessment. This study aims to validate the role of NFL and tau as biomarkers in HD. CSF was obtained from a cohort of HD patients and premanifest HD-mutation carriers. Unified Huntington's Disease Rating Scale (UHDRS) testing was performed on all subjects at the time of sampling. NFL and tau concentrations were determined by ELISA. Spearman correlations were calculated with R version 3.2.3. 11 premanifest HD and 12 manifest HD subjects were enrolled. NFL and tau levels were correlated. NFL showed strong correlations with all items included in the clinical assessment (for example the total functional capacity (TFC) (r = - 0.70 p < 0.01) and total motor score (TMS) (r = 0.83p < 0.01). Tau showed slightly weaker correlations (eg. TMS (r = 0.67 p < 0.01); TFC (r = - 0.59 p < 0.01)). NFL was significantly correlated with 5-year probability of disease onset, whereas tau was not. This study strengthens the case for NFL as a useful biomarker of disease stage. NFL was strongly correlated to all evaluated items in the UHDRS assessment. Tau also has a potential for use as a biomarker but correlations to clinical tests are weaker in this study. We suggest that NFL and possibly tau be used in clinical drug trials as biomarkers of disease progression that are potentially influenced by future disease-modifying therapies.